Professional Development in Certificate Educational Studies Leadership (CESL) for School Literacy Movement - Latifah, Nur; Ms, Zulela; Agustiningsih, Walisa Tri (Unnes Science Education Journal, 2020)
The purpose of this research is to analyze the improvement of the professional competencies of teachers who participated in the "Certificate in Educational Studies in Leadership (CESL)â€ for literacy movement at Tugu Utara 19 primary school. Researchers in this study used a qualitative approach with descriptive methods aimed at telling a story of a data, event or phenomenon unearthed through in-depth interviews with sources with knowledge and understanding and deep experience of the phenomenon. Data collection techniques use observation, interview, and documentation techniques. The results showed that the competence of professional teachers in carrying out literacy was a cognitive pre-action literacy movement in schools, 83.3% very good which answered almost 80% of teachers and educational personnel that they liked literacy corridors, and as many as 87.5%, which is 87.5% answering very happy, suggestions and upgrades to the next school project at Tugu Utara 19 primary school.